Os fundos patrimoniais endowment no Brasil - Spalding, Erika (2016)
The present study aims to provide a wide panorama of the endowment funds in Brazil, addressing not only the concept of this kind of fund and its role in the development context of the Brazilian third sector, but also the current legal barriers that hinder the full consolidation of the endowment as an important tool for the sustainable management of nonprofit organizations’ assets. The methodology adopted for this purpose relies on a course that goes from a more abstract approach – the gathering and analysis of the (actual and expected) legislation concerning the endowment funds – and ends with a more concrete one – the study of the demands and challenges faced by a few endowments funds based in the state of São Paulo that were interviewed by the author.